Enhancing elementary students' reading skills through Quizizz paper mode in English class - Baiq Indira Jesika Putri; Valentina Dyah Arum Sari (Journal of English in Academic and Professional Communication, 2025)
The Independent Learning Curriculum emphasized mastering foundational competencies, including English as a foreign language, to support students' academic development. In this curriculum, each phase of learning has specific learning objectives. Fifth-grade elementary school students, which is categorized as Phase C, need to achieve specific learning objectives in reading skills. However, preliminary studies revealed that many students struggle to meet these objectives, as indicated by their below-average performance and difficulties in mastering reading techniques. To address this issue, this paper aimed to reveal the improvement of students' reading skills through the implementation of Quizizz Paper-Mode and to find out the benefits of Quizizz Paper-Mode in enhancing elementary school students' reading skills. A mixed-method approach was employed to integrate qualitative and quantitative data, which were collected through tests, interviews, and questionnaires. The results of the study revealed the following: (1) Quizizz Paper-Mode improved students' reading abilities by 26.36%; (2) 80.4% of students responded positively to the implementation of Quizizz Paper-Mode, categorized as high; and (3) Quizizz Paper-Mode provided benefits to students' reading skills, with 71.5% categorized as medium. This study highlights the instructional value of Quizizz Paper-Mode as an effective alternative to enhance reading competencies in elementary education, especially in settings where digital infrastructure is limited.